Scripture, ethics, and the possibility of same-sex relationships - Keen, Karen R., 1973- (Eerdmans Publishing Co., 2018)
When it comes to same-sex relationships, this book by Karen Keen contains the most thoughtful, balanced, biblically grounded discussion you're likely to encounter anywhere. With pastoral sensitivity and respect for biblical authority, Keen breaks through current stalemates in the debate surrounding faith and sexual identity. The fresh, evenhanded reevaluation of Scripture, Christian tradition, theology, and science in Keen's Scripture, Ethics, and the Possibility of Same-Sex Relationships will appeal to both traditionalist and progressive church leaders and parishioners, students of ethics and biblical studies, and gay and lesbian people who often feel painfully torn between faith and sexuality. -- Publisher.